Vodne muhe poplesovalke (Diptera: Empididae) Slovenskega primorja in Istre - Horvat, Bogdan (Annales. Series historia naturalis, 1994)
The author presents the survey of the species of dancing water flies (Diptera:Empididae) in Slovenian Littoral and Istria together with a short commentary on their appearance in Europe and individual species (according to IUCN categories) from the point of view of nature protection. In the area of Slovenian Littoral and Istria 19 species of dancing water flies were determined. The discussed dancers belong to seven genera: Chelifera, Heleodromia, Hemerodromia and Phyllodromia from the subfamily of Hemerodromiinae, Clinocera, Dolichocephala and Wiedemannia from the subfamily of Clinocerinae.
Keywords: dvokrilci; favna; Istra; Istria; Slovensko primorje; vodne muhe; žuželke